IAPT/IOPB Chromosome Data 14: Rubiaceae. - Sobrado, Sandra Virginia (2012)
It is present: The first chromosome number count for 5 species, the first chromosome count from a South American accession for 1 specie and the first chromosome count from an Argentinian accession for 1 specie.